The evaluation of vaccination status and the factors affecting vaccination in cancer patients - Meltem Baykara; Hacer Demir; Sena Ece Davarcı; İsmail Beypınar; Muslih Ürün (Acta Medica Alanya)
Aim: Coronavirus disease 2019 (COVID-19) pandemic increased the mortality of cancer patients by causing direct infection or collateral damage to the healthcare system. After the development of effective vaccines against COVID-19 infection, mortality rates declined. In this study, we try to investigate the vaccination among cancer patients.Methods: A survey was applied to patients with cancer in order to investigate the attitudes towards vaccination and the factors effecting vaccination in two medical oncology centers in Turkey.Results: 271 patients were included in the study. No difference was observed in the attitudes of patients towards vaccination according to cancer type. 83% of the patients were vaccinated against COVID-19. In 75% of the study population, vaccine was administered in the earliest available time. Receiving chemotherapy was the most significant reason to avoid vaccination among the study group (p=0,002). There was no significant difference in terms of treatment type for COVID-19 between patients with or without adequate vaccination. The most negative factor affecting vaccination was active chemotherapy treatment. Social relations and traditional media were the most positive factors for vaccination.Discussion: Vaccination is of vital importance for patients who are treated or on remission. Even if patients are to receive chemotherapy, they should be informed about vaccination and should be encouraged for vaccination.